Daya Saing dan Determinan Ekspor Kopi Indonesia Di Jepang (Jurnal Agribisnis Indonesia, 2024)
Indonesian coffee export has reached various countries, one of its destinations is Japan with export share around 8,58%. Moreover, Indonesia and Japan have taken an effort to normalize their bilateral trade through Indonesia-Japan Economic Partnership Agreement (IJEPA). However, the average of Indonesian coffee export to Japan shows a downturn around 3,81% per years which expected due to non-tarif barriers and low utilization of IJEPA. This research aims to examine the competitiveness and determinants of Indonesian coffee export to Japan on long and short term and employs multiple linear regression using Error Correction Mechanism (ECM) approach. The research result shows that Indonesian coffee has medium comparative advantage in Japan market with downturn growth during 2001-2022 period. Furthermore, world coffee price and Indonesian coffee competitiveness in Japan become the significantly positive factors that affect Indonesian coffee export on long and short term. The other factors that affect Indonesian coffee export on long term are Indonesia real GDP, Japan real GDP, and dummy IJEPA agreement. Therefore, the quality improvement of Indonesian coffee with single origin and environmentally responsible characteristics is urgent to boost competitiveness and reduce the effect of world coffee price changes.